1996
DOI: 10.1029/96jb01183
|View full text |Cite
|
Sign up to set email alerts
|

Geodesy using the Swedish permanent GPS network: Effects of signal scattering on estimates of relative site positions

Abstract: This paper presents results from a study of elevation‐angle‐dependent systematic effects on estimates of relative site positions within the Swedish permanent Global Positioning System (GPS) network. Two months of data from 16 sites have been analyzed with three different elevation cutoff angles, namely, 10°, 15°, and 20°. We present offsets between these solutions and demonstrate that estimates of the vertical component of several baselines strongly depend on the minimum elevation angle (elevation cutoff angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…We selected GPS stations that are close to the radiosonde stations deployed by the Japan Meteorological Agency (JMA), taking account of (1) the distance between GPS and radiosonde stations is as far as 40 km and (2) the height difference between them is below 100 m. Also, to avoid antenna mixing problems and signal scattering associated with the antenna mount [Jaldehag et al, 1996], we selected stations belonging to the same cluster so that the antenna type and mounting system are identical.…”
Section: Comparisons Of Pwv Derived From Routine Gps Analysis With Rasupporting
confidence: 88%
“…We selected GPS stations that are close to the radiosonde stations deployed by the Japan Meteorological Agency (JMA), taking account of (1) the distance between GPS and radiosonde stations is as far as 40 km and (2) the height difference between them is below 100 m. Also, to avoid antenna mixing problems and signal scattering associated with the antenna mount [Jaldehag et al, 1996], we selected stations belonging to the same cluster so that the antenna type and mounting system are identical.…”
Section: Comparisons Of Pwv Derived From Routine Gps Analysis With Rasupporting
confidence: 88%
“…In addition to the error introduced by the radome itself, additional error may be incurred as matter accumulates on the radome. For example, the effect on height measurements of the accumulation of snow on the radome is documented by Jaldehag et al (1996a). The equivalent change in ZWD for the errors observed during one month in January 1994 (50 mm in height) amounts to 20 mm.…”
Section: ) Effect Of Radomementioning
confidence: 99%
“…Elósegui et al (1995) and Jaldehag et al (1996a) showed that the signal scattering from the top of the antenna pillar affects the phase observable and the estimate of vertical component of site position, and that putting electrical wave absorbing materials on the pillar is effective in reducing this problem. Carrier phase of GPS signals is also affected by radomes used for protecting GPS antennas, and thus affects the results of the analysis (Meertens et al, 1996;Johansson et al, 1998).…”
Section: Introductionmentioning
confidence: 99%